Validity of session-rate of perceived exertion to quantify training loads in paralympic swimmers - Sinnott-O'Connor, C.; Comyns, T. M.; Warrington, G. D. (The Journal of Strength and Conditioning Research, 2021)
Multiple measures may be used by coaches to quantify training load (TL). The application of heart rate (HR) has limitations in swimming and in Paralympic swimmers, and it may not always be a suitable measure. Therefore, the aim of this study was to determine the validity and reliability of the session-rate of perceived exertion (sRPE) method for quantifying internal TL in Paralympic swimmers. A further aim was to examine the relationship between athlete and coach perceptions of sRPE TL. Four international Paralympic swimmers selected to compete in Rio 2016 Paralympic Games participated in this study. Heart rate, RPE, and session duration were recorded for 30 training sessions of varied intensities across a 6-week home training period to quantify TL. Significant high to very high positive correlations were observed between sRPE and 3 HR-based measures—Banister's, Edwards, and Lucia's TRIMP (r = 0.68, 0.66, 0.74, p < 0.01, respectively). Moderate correlations were observed between sRPE and distance measures (r = 0.53, p < 0.05) but were lower than those observed with HR-based measures. A 2-way analysis of variance identified significant differences in the sRPE ratings between coaches and athletes (F(2, 108) = 170.4, p < 0.01, Eta2 = 0.75). The results of this study suggest that the sRPE method may be an appropriate monitoring tool for quantifying TL during water-based training using a single measure in Paralympic swimmers.